Feed utilization efficiency and ruminal metabolites in beef cattle fed with cassava pulp fermented yeast waste replacement soybean meal - Gamonmas Dagaew; Sawitree Wongtangtintharn; Chanon Suntara; Rittikeard Prachumchai; Metha Wanapat; Anusorn Cherdthong (Scientific Reports, 2022)
Abstract The purpose of this study was to see how substituting cassava pulp fermented yeast waste (CSYW) for soybean meal (SBM) in a concentrate affected feed intake, digestibility, and rumen fermentation in Thai native beef cattle. In this study, four male Thai native beef cattle with an average age of 15.0 ± 25.0 months and body weights of 140 ± 5.0 kg were used. The experimental design was a 4 × 4 Latin squared design, with dietary treatments of CSYW replacing SBM at 0, 33, 67, and 100% in the concentrate mixture. It was discovered that the presence of CSYW had no negative impact on feed intake, nutritional intake, or apparent digestibility (p > 0.05). CSYW had no significant effects on ruminal pH or temperature (p > 0.05). When the amount of CSYW in the diet increased, the rumen ammonia–nitrogen concentration increased (p < 0.05). Blood urea nitrogen was not affected by CSYW (p > 0.05). The total bacterial population increased when the diet's CSYW amount was increased (p < 0.05). Feeding CSYW to beef cattle had no influence on total volatile fatty acid, acetic acid (C2), or butyric acid (C4) proportions (p > 0.05). The concentration of propionic acid (C3) and the C2:C3 ratio increased when the amount of CSYW in the diet was increased (p < 0.05). In conclusion, CSYW can completely replace SBM in a concentrate diet for beef cattle with no adverse effects on feed utilization or rumen fermentation while the total bacterial population and C3 concentration increase.